Preparation and water vapor adsorption of “green” walnut-shell activated carbon by CO physical activation - Hong Zhao; Qiongfen Yu; Ming Li; Shengnan Sun (Adsorption Science & Technology)
In this study, activated carbons without any chemical residue were prepared from walnut shells. The preparation method in a tube furnace included a pyrolysis carbonization process and a CO 2 activation process. The influences of activation temperature and holding time on the specific surface area, yield, and pore structure were investigated. Adsorption performance of water vapor was also examined in details. Thermogravimetric analysis, N 2 adsorption–desorption isotherm, and scanning electron microscope were used to characterize samples. The result shows that the activation energy at different heating rates varies from 30.16 to 64.86 kJ/mol. The highest water vapor adsorption capacity of the sample is 0.3824 g/g and it takes only 30 min to realize regeneration. And the maximum Brunauer–Emmett–Teller specific surface area of 1228 m 2 /g also occurs in this optimal preparation condition. CO 2 physical activation method was found to have a positive effect on pore structure development of activated carbon for water vapor adsorption.